Touching soft materials slows affective visual processing - Pasqualotto, Achille; Leong, Utek; Kitada, Ryo (Frontiers in Psychology, 2025)
Presently, there is extensive evidence of multisensory integration in tactile and visual processing. While it has been shown that multisensory interaction between touch and vision influences many cognitive processes, such as object recognition, the role of multisensory interaction in the affective domain is still poorly understood. The aim of this study was to examine the influence of tactile perception on the affective processing of visual stimuli. Two experiments were conducted with urethane rubbers of differing compliance and with visually presented words. In the first experiment, participants rated the affective valence of the visually presented words while touching hard or soft urethane rubbers. Ratings and reaction times were recorded. Results showed touching a soft stimulus slowed the valence rating of visual words, but it did not affect the valence ratings per se. A second experiment clarified whether this effect was unique to valence (affective) ratings or whether it extended to semantic (cognitive) ratings as well. The second experiment was identical to the first one, but here participants rated the level of abstractness of the same visually presented words. Results indicated that abstractness ratings were not affected by the tactile stimuli. Overall, these confirm that, possibly via an attentional mechanism, tactile input influences the speed of affective visual processing.